PENGARUH KETIDAKJELASAN PERAN, KONFLIK PERAN PADA KINERJA AUDITOR DENGAN STRUKTUR AUDIT SEBAGAI PEMODERASI - Trisnawati, Meita; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 10 No 3 (2015), 2015)
This scientific work to figure out the relationship and role ambiguity role conflict on the performance of auditors, as well as to determine the structure of the audit in moderating influence role ambiguity and role conflict in the auditor's performance. KAP research sites in Bali Province. Respondents of the study amounted to 84 people. The data collected in this study using a questionnaire. Questionnaires were distributed to 84 pieces, while the questionnaires were returned and can be processed as many as 70 pieces. This paper uses saturated sample or census method in determining the sample. Testing this paper uses regression analysis with SPSS moderation. This paper shows the role ambiguity is positively and significantly affects the performance of auditors and role conflict negatively and significantly affect the performance of the auditor, and audit structure able to moderate the strengthening role ambiguity and role conflict in the auditor's performance.
Keywords: role ambiguity, role conflict, performance auditor, audit structure